LANDASAN TEOLOGIS DAN PRAKTIK PENDIDIKAN MULTIKULTURAL - Gozali Gozali; Imam Sibaweh; Adang Hambali; Hasan Basri (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
Indonesia’s diverse landscape presents challenges in creating a multicultural education system. This study explores how Islamic teachings from the Qur’an and Sunnah can enhance multicultural education in Indonesia. Using library research, the study analyzes literature for qualitative data. A descriptive-analytical approach is applied to understand the theological foundations, sourcing data from books, sacred texts, and journals. Key principles identified include equality (al-musawah), justice (al-’adl), compassion (al-rahmah), and tolerance (al-tasamuh). Verses like QS. Al-Hujurat: 13 emphasize human equality, QS. An-Nahl: 90 highlights justice and kindness, QS. Ali-Imran: 159 advocates gentleness and forgiveness, and QS. Al-Kafirun: 1-6 promotes respect for religious differences. The Prophet’s practices in Medina, including the Charter of Medina, illustrate these principles in fostering cooperation and peaceful coexistence. The research concludes that the Qur’an and the Prophet’s teachings provide a robust foundation for multicultural education in Indonesia.